HUBUNGAN KUALITAS HIDUP PASIEN CA MAMMAE DENGAN EFEK SAMPING KEMOTERAPI DI MURNI TEGUH MEMORIAL HOSPITAL - Pasaribu, Rizka; Banjarnahor, Seriga (Indonesian Trust Nursing Journal, 2025)
Chemotherapy is a treatment process to slow and destroy the growth of cancer cells with cytotoxic drugs. Breast cancer treatment generally lasts quite a long time and causes side effects, namely physical and psychological impacts on breast cancer patients related to quality of life. The objective of this study is to determine the assessment of the quality of life of breast cancer patients with the side effects of chemotherapy. This study method is a quantitative analytical survey study with a cross-sectional approach. The study was conducted at Murni Teguh Memorial Hospital. The population was 20 people and all were used as samples. Sampling was carried out using a saturated sample (total sampling). Data were analyzed using the Chi-square test with a significance of  = 0.05. This study shows that the quality of life of breast cancer patients is in the good and poor categories, each 50%. The side effects of chemotherapy felt by breast cancer patients are in the low category (45%). There is a relationship between the assessment of the quality of life of breast cancer patients and the side effects of chemotherapy at Murni Teguh Memorial Hospital, p-value = 0.003 <0.05. It is concluded that the side effects of chemotherapy are related to the assessment of the quality of life of breast cancer patients. It is recommended that further researchers continue this study using a larger sample size.